Fictitious-Transfers in Cooperative Game Theory - Roger B. Myerson (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1990)
The method of fictitious transfers (or lambda-transfers) is used in cooperative game theory to extend solution concepts from the transferable utility case to the more general case of games without transferable utility. The importance of this idea is examined in the context of the history of its development and some recent results. A new interpretation of the inner core (or lambda-transfer core) is discussed.
Keywords: 330